(e) Show that $\vdash \lnot(p \lor \lnot p) \to p \land \lnot p$

(f) Show that $\models p \lor \lnot p$ and $\vdash p \lor \lnot p$. For the second part, you can assume (e), i.e. you can treat $\lnot (p \lor \lnot p) \to p \land \lnot p$ as an assumption.

The first part is natural deduction, I just can't figure out how to go about it, and the second part I'm really not sure about.

Thank you

$$% I'll add a link because I'm not sure how to put the symbols. [https://imgur.com/a/ijaE1vQ][1] [1]: https://imgur.com/a/ijaE1vQ$$



Assume $\lnot (p \lor \lnot p)$ and assume $p$. From it derive a contradiction and conclude with $\lnot p$ discharging the assumption.

Then assume $\lnot p$ and repeat, using double negation to conclude with $p$.

For $\vDash p \lor \lnot p$ use truth table.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.